ANALISIS TEORI BEHAVIOR DAN PENDEKATAN BIMBINGAN KONSELING ISLAM DALAM MENYELESAIKAN MASALAH KEHIDUPAN REMAJA - Imam Rifai; Miftahul Rahmah; Hartini; Beni Azwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Effectiveness of the Islamic Guidance and Counseling approach combined with behavioral theory in addressing behavioral and spiritual problems among adolescents at MTs Muhammadiyah Curup. Behavioral theory emphasizes that behavior can be shaped through stimulus and response using reinforcement and punishment principles. Within the Islamic framework, this approach is enriched by spiritual values derived from the Qur'an and Hadith, thus addressing not only behavioral aspects but also the spiritual dimension of faith. This research employed a library research method alongside documentation, observation, and interviews in the field. The findings indicate that the combination of behavioral theory and Islamic counseling significantly aids students in improving discipline, responsibility, and emotional control, while also enhancing spiritual values and religious motivation. This approach is considered effective as it reaches the students' internal awareness and fosters consistent personal transformation. The study recommends that the Islamic Guidance and Counseling approach be continuously implemented in Islamic educational settings to support adolescents in overcoming behavioral and spiritual challenges.